Timing of caffeine ingestion does not improve three-point shooting accuracy in college basketball players - Tan, Z. S.; Sim, R. Y. Y.; Kawabata, M.; Low, D. Y.; Wang, Y.; Burns, S. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
This study investigated the effects of the timing of caffeine (3 mg/kg body mass) ingestion on three-point shooting accuracy and other performance parameters during a basketball exercise simulation test (BEST). Eighteen college basketball players (mean ± SD: age = 24.4 ± 1.5 years, height = 181.7 ± 9.5 cm, body mass = 80.9 ± 13.2 kg) underwent one familiarization trial and three main conditions in a randomized order: (a) placebo (maltodextrin) and placebo, (b) caffeine and placebo, and (c) placebo and caffeine. Participants ingested either the placebo or caffeine pill 75 and 15 min before performing four quarters of the BEST and a three-point shooting protocol. During each quarter, participants completed 16 rounds of the BEST and ten three-point shots. Vertical jump height, 6 m sprint timing, BEST completion timing, three-point shooting accuracy, heart rate, rate of perceived exertion, blood glucose, blood lactate, and psychological measures pertaining to performance were measured. The BEST completion timing differed among conditions (placebo and placebo = 26.4 ± 2.0 s, caffeine and placebo = 25.8 ± 2.0 s, placebo and caffeine = 25.9 ± 2.1 s; p = .031) but not three-point shooting accuracy (placebo and placebo = 12.33 ± 4.10; caffeine and placebo = 12.61 ± 2.81; placebo and caffeine = 11.67 ± 3.77; p = .648), vertical jump height, or sprint times. Manipulating ingestion timing of caffeine did not improve three-point shooting accuracy, vertical jump height, or 6 m sprint timings, but caffeine can improve performance times during simulated basketball exercise irrespective of ingestion timing.